Redefining and Restructuring Engineering - Mebrahitom, Asmelash Gebremariam (Kolej Kejuruteraan, 2020)
Universiti Malaysia Pahang has refined its institutional priorities and restructured into a new set up of different colleges and faculties. Under the new structure, the pure Engineering fields are located at Gambang campus and regrouped under the College of Engineering, consisting of Civil Engineering, Chemical Engineering, Electrical Engineering, Industrial Engineering and Mechanical Engineering departments. Each programme is accredited by the Board of Engineers, Malaysia for undergraduate students and provides the graduates with a strong foundation that prepares them for successful profession in the future. Candidates also have an option to accomplish research work by continouing their studies to Masters and PhD levels.